Synthesis, Evaluation and Characterization of Some 1,3,4-Triazole-2-one Derivatives as Antimicrobial Agents - Mahabaleshwaraiah Neelgundmath; Oblennavar Kotresh (E-Journal of Chemistry)
A series of novel compounds like 3[(phenyl substituted)-5-methyl-1(Benzosulphonylamine)]-1,3,4-triazole-2-ones II(a-f) were synthesized by treating 4-amino-1-phenyl-3-methyl-5-oxo-1,2,4-triazoles with benzene sulphonyl chloride using pyridine as solvent. Similarly by using 4-amino-1-aryl-3-methyl-5-oxo-1,2,4-triazoles and acetic anhydride as starting material 3[(phenyl substituted)-5-methyl-1(acetylamino)]-1,3,4-triazole-2-ones III(a-f) were synthesized and also 3[(phenyl substituted)-5-methyl-1(chloroacetyl)]-1,3,4-triazole-2-ones I(a-f) were synthesized by treating 4-amino-1-aryl-3-methyl-5-oxo-1,2,4-triazoles with chloroacetyl chloride in presence of a non-polar solvent like benzene. Elemental analysis, GCMS, IR, and 1H NMR confirmed the structures of the newly synthesised compounds. The newly synthesized compounds are also screened for their antibacterial, antifungal and anti-inflammatory activities.